2SPD-003 Monitoring the use of linezolid in a third-level hospital. (March 2019) - Sanabrias, R; Folguera, C; Calvo, M; Menchén, B; García, MD; Repilado, A; Sánchez, A
Abstract : Background: The consequences of misuse of antibiotics can be very serious for patients and affect health systems and the community as a whole. Purpose: To analyse the evolution of linezolid (LNZ) consumption from 2009 to 2017 in general in the hospital and in critical care services (Anaesthesia-Resuscitation (A-R) and Intensive Care Unit (ICU)), and see if the introduction of the LNZ generic produced an increase in its use. Material and methods: Observational and retrospective study in a tertiary level hospital. The Farmatools program was used to obtain annual consumption from 2009 to 2017, both included, of the three available LNZ presentations (tablets, vials and oral suspension). The same information was obtained from the A-R and ICU services. The defined daily doses (DDD)/100 stays for the 9 years of the study were calculated on an annual basis. The differences in the LNZ consumption of each year with respect to the previous year were analysed in a general way for the hospital and for the A-R and ICU services. The introduction of the LNZ generic in the hospital was in 2016. Results: The table shows: (A)% variation of global LNZ consumption by years; (B) DDD/100 stays for years of LNZ; and% variation of consumption in A-R (C) and ICU (D) services. It is observed that as of 2015 there was a considerable increase in the consumption of LNZ. After analysing its use in critical patients, we observed that A-R increased consumption in 2017 (14.5%). In ICU there was a very significant increase (54.35%) during the year of availability of the generic and it was maintained during 2017. The introduction of the generic and the associated price decrease could relax the monitoring of the prescription of this antibiotic. Conclusion: The increase in LNZ consumption appeared one year before the availability of the generic. In the critical units, the consumption was affected differently, increasing in A-R less and one year later than in ICU, in which it increased very significantly and coinciding with the access to the generic. The introduction of the LNZ generic contributed, along with other factors, to explaining the increase in consumption of it in our hospital. References and/or acknowledgements: https://ejhp.bmj.com/content/24/Suppl_1/A67.1 https://ejhp.bmj.com/content/24/Suppl_1/A230.1 https://ejhp.bmj.com/content/22/Suppl_1/A93.1 No conflict of interest.